Register and gender perspectives in Kate Chopin's The Awakening - Guirnalda, Ma. Fe Concepcion L. (College of Arts and Letters, University of the Philippines Diliman, 1996)
This thesis presents the study of male and female registers in a Kate Chopin novel utilizing Norman Fairclough's modifications on Halliday's register theory. The purpose of examining the registers of the men and women characters in "The Awakening" is to provide explanations as to how a female character can use her registers to claim her freedom from the roles accorded to her by a patriarchal society. Analysis of male and female registers uncovered their functions. Analysis shows how register is utilized by the males in order to promote and maintain their hold on power. Analysis shows how a female uses new registers in order to challenge the ideologies of the time. Thus, the study of register unveils the processes by which one claims power and imposes it on others, and how an individual can free herself from the clutches of such power. The theory of register therefore is significant for through its application in the study of literature, one is given an understanding of society as well.